A Three‐Terminal Hybrid Thermionic‐Photovoltaic Energy Converter. Issue 20 (11th April 2022) - Bellucci, Alessandro; García‐Linares, Pablo; Martí, Antonio; Trucchi, Daniele Maria; Datas, Alejandro
Abstract: Hybrid thermionic‐photovoltaics (TIPV) are solid‐state thermal‐to‐electric energy converters that rely on the non‐isothermal transport of photons and electrons through a vacuum gap. In contrast to pure thermionic converters, the absorption of photons in a photovoltaic anode produces an electrochemical potential that can be delivered as electricity, ultimately boosting the power generation capacity of the device. In this work, the proof of concept of a three‐terminal TIPV converter where thermionic and photogenerated currents are collected independently is reported. Thermionic electrons are injected in the conduction band of a semiconducting anode (n‐type InP), from where they are directly extracted. Photogenerated electrons are also extracted from the conduction band of the anode, but they are then reinjected in the valence band through an independent hole‐selective contact (p‐type InGaAs). By using a low workfunction engineered anode (BaF x /InP) and cathode (Sc x O y /W) a maximum power generation capacity of 125.6 and 0.35 mW cm −2 for PV and thermionic sub‐devices, respectively, is demonstrated, operating at 1400 °C. This proof of concept paves the way for the development of efficient hybrid thermionic and photovoltaic converters for the direct conversion of heat into electricity, and subsequently contributes to finding an efficient alternative to thermoelectric generators. Abstract : The experimental proof of a three‐terminal thermionic‐photovoltaic converter is provided. The device produces electricity from the non‐isothermal transport of photons and electrons through a vacuum gap. An output power of 125.6 and 0.35 mW cm −2 is measured for the photovoltaic and thermionic sub‐devices, respectively, operating at 1400 °C.